The Role of Dance Extracurriculars in Forming the Character of Love for the Homeland at SMP Muhammadiyah 4 Yogyakarta - Shinta, Vika Anggela; Arif, Dikdik Baehaqi (Universitas Muhammadiyah Surakarta, 2023)
In the current era of globalization, loving one's motherland is necessary. The reality on the ground demonstrates that student nationalism frequently encounters unfavorable dynamics. Some students did not participate solemnly in the flag ceremony, did not listen to the national anthem, or speak Indonesian correctly in their daily interactions. Enhancing character education in extracurricular activities is one of the ways that these students' love for their country is shaped. This study aimed to learn more about SMP Muhammadiyah 4 Yogyakarta's dance extracurricular efforts in developing the character of love for the motherland. This study employed a qualitative case study: observation, documentation, and interview-based data collection methods. Principals of schools, teachers of art and culture, dance coaches, and two SMP Muhammadiyah 4 Yogyakarta students served as the research participants. This study examines how extracurricular dance instruction shapes a person's love of country. Data collection, reduction, presentation, and conclusion were all used as data analysis techniques. The findings show that the DIY Regional Regulation Number 5 of 2011 can be used to understand the extracurricular role of dance in forming the character of loving the homeland by introducing and providing an understanding related to the formation of that character through art. Facilities, adequate infrastructure, student enthusiasm, and school support all contribute to developing the character trait of loving one's country. In addition, events and circumstances, such as PPKM, that prohibit these activities from going as they should are the elements that impede pupils from developing a love for their country.